Biofilm: a Virulent Form of Bacteria Life In Which Leads an Emerging Battleground of Antibiotic Resistance - I Putu Bayu Mayura; Putu Yuliandari (International Journal of Health and Pharmaceutical (IJHP), 2026)
Biofilms represent a highly virulent bacterial lifestyle that substantially contributes to the global escalation of antimicrobial resistance by protecting pathogens from conventional therapies. This study aimed to synthesize current evidence on biofilm structure, developmental stages, and mechanisms underlying antibiotic recalcitrance in clinically important bacteria, including Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. A systematic qualitative literature review was conducted using peer-reviewed articles published between 2016 and 2022 retrieved from Google Scholar, PubMed, and related scientific databases. Approximately 20 relevant studies were purposively selected based on predefined inclusion criteria, and thematic content analysis was applied to identify recurrent resistance mechanisms. The findings showed that biofilm resilience was driven by the synergistic interaction of extracellular matrix barriers, metabolic heterogeneity, persister cells, quorum sensing regulation, altered membrane permeability, stress responses, and multidrug efflux pumps. These mechanisms enabled bacteria to exhibit both genetic resistance and phenotypic tolerance, often increasing antimicrobial survival capacity up to several thousand-fold compared with planktonic cells. The review concluded that biofilm-associated infections cannot be effectively managed through single-antibiotic approaches alone. Integrated therapeutic strategies combining antibiotics with matrix-disrupting agents, quorum sensing inhibitors, and early detection technologies are required to reduce chronic infections and healthcare-associated transmission. These findings provide a conceptual basis for developing precision anti-biofilm interventions and future translational research.